Picture-book professors : academia and children's literature - Terras, Melissa M. (Cambridge University Press, 2018)
How is academia portrayed in children's literature? This Element ambitiously surveys fictional professors in texts marketed towards children. Professors are overwhelmingly white and male, tending to be elderly scientists who fall into three stereotypes: the vehicle to explain scientific facts, the baffled genius, and the evil madman. By the late twentieth century, the stereotype of the male, mad, muddlehead, called Professor SomethingDumb, is formed in humorous yet pejorative fashion. This Element provides a publishing history of the role of academics in children's literature, questioning the book culture which promotes the enforcement of stereotypes regarding intellectual expertise in children's media. The Element is also available, with additional material, as Open Access.
Title from publisher's bibliographic system (viewed on 15 Oct 2018).
Open Access title.
Keywords: Children's literature -- History and criticism; College teachers in literature; Stereotypes (Social psychology) in literature